2021
DOI: 10.3390/nano11051279
|View full text |Cite
|
Sign up to set email alerts
|

Li4(OH)3Br-Based Shape Stabilized Composites for High-Temperature TES Applications: Selection of the Most Convenient Supporting Material

Abstract: Peritectic compound Li4(OH)3Br has been recently proposed as phase change material (PCM) for thermal energy storage (TES) applications at approx. 300 °C Compared to competitor PCM materials (e.g., sodium nitrate), the main assets of this compound are high volumetric latent heat storage capacity (>140 kWh/m3) and very low volume changes (<3%) during peritectic reaction and melting. The objective of the present work was to find proper supporting materials able to shape stabilize Li4(OH)3Br during the forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
(88 reference statements)
0
2
0
Order By: Relevance
“…Mahroug et al [23] reported a selection of the most promising oxide-based supporting materials for the Li 4 (OH) 3 Br peritectic compound to be used in thermal energy storage (TES) applications at ca. 300 • C. The authors investigated micro/nanoparticles of MgO, Fe 2 O 3 , CuO, SiO 2 and Al 2 O 3 as candidates for supporting materials.…”
Section: Commenmentioning
confidence: 99%
“…Mahroug et al [23] reported a selection of the most promising oxide-based supporting materials for the Li 4 (OH) 3 Br peritectic compound to be used in thermal energy storage (TES) applications at ca. 300 • C. The authors investigated micro/nanoparticles of MgO, Fe 2 O 3 , CuO, SiO 2 and Al 2 O 3 as candidates for supporting materials.…”
Section: Commenmentioning
confidence: 99%
“…In recent years, a large number of research papers have proposed a composite phase change TES technology that uses skeleton materials (SMs) to encapsulate phase change materials (PCMs); the PCMs are wrapped in the pores of the SMs to avoid leakage. Al 2 O 3 [36,37], MgO [38,39], Ca(OH) 2 [40], expanded graphite [41,42], expanded vermiculite [43,44], tailings [45,46], SiC [47,48], semi-coke ash [49,50], fly ash [51][52][53], and kaolinite [54,55] are all used as SMs to prepare energy storage composites (ESCs) for TES. SS and RM can also be used as SMs after pretreatment and combined with PCMs to prepare ESCs.…”
Section: Introductionmentioning
confidence: 99%